2013
DOI: 10.1089/apc.2013.0169
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Provider Attitudes, Practices, and Recommendations for Enhancing Routine HIV Testing and Linkage to Care in the Mississippi Delta Region

Abstract: The Mississippi Delta region is one of the communities most heavily impacted by HIV/AIDS in the United States. To understand local provider attitudes and practices regarding HIV testing and care, we conducted 25 in-depth qualitative interviews with local primary care providers and infectious disease specialists. Interviews explored attitudes and practices regarding HIV testing and linkage to care. Most providers did not routinely offer HIV testing, noting financial barriers, financial disincentives to offer ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…13,24,[37][38][39] Even if counseling and testing sites are close to a rural resident's home, rural residents may prefer to be tested in a different community to ensure anonymity, which can result in delayed testing. Rural providers have suggested that integrating HIV testing into other health services; rapid oral testing and community health education; outreach; and making HIV testing more convenient, accessible, and free are potential ways to decrease barriers.…”
Section: Discussionmentioning
confidence: 99%
“…13,24,[37][38][39] Even if counseling and testing sites are close to a rural resident's home, rural residents may prefer to be tested in a different community to ensure anonymity, which can result in delayed testing. Rural providers have suggested that integrating HIV testing into other health services; rapid oral testing and community health education; outreach; and making HIV testing more convenient, accessible, and free are potential ways to decrease barriers.…”
Section: Discussionmentioning
confidence: 99%
“…A letter by the HIV Testing Reimbursement Subcommittee of the HIV Health Care Access Working Group (affiliated with the Federal AIDS Policy Partnership) states that “due to the provisions of the [Affordable Care Act], all major payers will be either required to or incentivized to cover HIV Testing.” 17(pl) Furthermore, a recent study suggests providers are much more willing to provide HIV testing services when reimbursement is offered. 18 This again emphasizes how critical it is to understand the barriers that have thus far limited more universal physician-led implementation of routine HIV testing.…”
Section: Hiv Testing Recommendations and Policiesmentioning
confidence: 99%
“…The implementation of this service is dependent on the knowledge and motivation of the health care workers who provide the service (Sison et al 2013). Patients are required to provide verbal consent for testing to occur, with the results forming part of the patient's records in-order to make a correct diagnosis and provide the HIV positive patients with appropriate treatment.…”
Section: Introductionmentioning
confidence: 99%